Evaluación de la satisfacción y calidad del servicio al cliente mediante el modelo SERVQUAL en la distribuidora K-CENTRO PIKA. - Sarabia Sánchez, Dayana Lizbeth (2018)
The objective of this research project is to evaluate the quality of the service at Distribuidora KCentro Pika.To develop, a qualitative methodology was applied, and the research was descriptive, explanatory, where was necessary data getting and its analysis. To determine the results, the Servqual model was used to measure the expectations and perceptions of the clients based on 5 dimensions: reliability, response capacity, security, empathy and tangible elements, which allows to adapt easily to any area, the purpose is to identify the clients needs and demands while controlling and monitoring in order to avoid the presence of problems and improve the quality of services. On the other hand, surveys were applied to a sample of 382 same clients that were selected randomly, at this sense, the information was analyzed and it was determined that in the Distribuidora K- Centro Pika there is a satisfactory level of service quality in each of the evaluated dimensions. It was also possible to identify as a greatest weakness the response capacity, where the clients expressed their disagreement, aspects that generate the deficiency that exists between perceived quality and the expected quality, making it impossible to reach a totally satisfactory level. Finally, a matrix of strengths and weaknesses was made that will allow to take corrective measures to improve the quality of the service at the distribuidora